Preventive and therapeutic assessment program for mucositis in patients with cancer: promising advances in stomatological care - Renata Lemos Ferrari; Rafaela Mota Peixoto; Tauana Batista Fernandes; Luana Farnese Machado Abreu; Ana Carolina de Araujo Tolentino Felizardo; Lourenço Duarte Siqueira; Ana Maria Dias da Costa; Bianca Silva de Andrade; Clara de Figueiredo Lopes; Daniele Ferreira Araujo; Leticia Fulgencio de Araújo; Ruan Soares da Silva; et al. (Brazilian Journal of Oncology)
OBJECTIVES: We propose a preventive and therapeutic assessment program for mucositis in patients with cancer based on a comprehensive review of scientific evidence. MATERIAL AND METHODS: This methodological study, designed as a non-systematic review, entails a thorough review of the scientific evidence on the management of mucositis in patients with cancer. The PICO method was used, allowing for a structured approach to explore and synthesize relevant evidence. RESULTS: Effective mucositis management requires regular assessments, dental exams, preventive strategies, and consideration of modifiable risk factors. Pharmacological therapies may be considered for severe cases, while oral antimicrobials, prophylactic antiviral and antifungal therapy can prevent infections. Topical anesthetics o?er pain relief but require careful administration. A gradual management plan, from gentle rinses to analgesics, is recommended. CONCLUSION: The suggested program may improve the identification, prevention, and management of this complication to achieve optimal management outcomes.